Salinity Stress Response of Rice (Oryza sativa L. cv. Luem Pua) Calli and Seedlings - Worasitikulya Taratima; Titirat Chomarsa; Pitakpong Maneerattanarungroj (Scientifica)
Soil salinity limits plant growth and production. This research investigated a suitable medium for callus induction and plantlet regeneration in the Luem Pua rice cultivar. The effect of salt stress on seedling growth was determined using in vitro culture and soil conditions. An efficient protocol for callus induction has been developed by culture sterilized seeds on the Murashige and Skoog (MS, 1962) medium containing 0.5 mg/l benzyladenine (BA) with 1 mg/l 2,4-dichlorophenoxyacetic acid (2,4-D) that resulted in a 100% callus induction. Plantlet regeneration percentage of 49% was recorded on the MS medium containing 4 mg/l BA with 0.5 mg/l 1-naphthaleneacetic acid (NAA) after 4 weeks. For salt stress investigation, the calli were treated on an induction medium containing various concentrations of NaCl (0, 50, 100, 150, and 200 mM), while two-week-old rice seedlings were planted in soil and treated with the same concentration of NaCl for 4 weeks. In vitro culture revealed that callus survival percentage decreased when NaCl concentration increased, similar to soil culture. Seedling growth under salinity treatment also decreased when NaCl concentration increased, while other physiological parameters such as total chlorophyll, chlorophyll a, chlorophyll b, green intensity, and chlorophyll fluorescence under light conditions increased under salinity stress. These changes define the growth and physiological salinity tolerance characteristics of Luem Pua rice calli and seedlings. They can be utilized as a baseline for demand-driven in vitro rice propagation, providing useful information that can be combined with other agronomic features in rice development or breeding programs to improve the flexibility of abiotic stress-tolerant cultivars.